Fertility Decline, Small Families, and Son Selection in the Arab World: The Controversial Convergence of Contraceptive and Repro‐genetic Technologies - Inhorn, Marcia C. (The Muslim world (Hartford), 2022)
The Arab world has experienced one of the most dramatic fertility declines in modern history, the result of both contraceptive technologies and couples’ desires for smaller families. Assisted reproductive and genetic technologies have also become widespread across the region, leading to new practices of in vitro fertilization (IVF) with sex selection. This article examines the desire for small families with sons, and the introduction of the repro‐genetic technology of preimplantation genetic screening (PGS) for son selection. Islamic opinions on sex selection are divided, but permissive fatwas have fueled practices of son selection in some Arab countries, including the United Arab Emirates, the focus of this study. As shown in this article, the “bioethical aftermath” of these repro‐genetic practices may include son preference and daughter discrimination, with future distortions of population sex ratios across the Arab world.